A new energy dissipative cable bracing system. Issue 14 (October 2019) - Bagheri, Saman; Shishvan, Siamak S; Barghian, Majid; Baniahmad, Behzad
A special type of cable bracing system comprising a pre-stressed cable and a drum interacting via frictional contact is proposed for lateral resistance of structures, and an analytical solution for the response of this system is developed. The response of the system is highly non-linear due to the existence of frictional contact as well as geometrical effects and it consists of two phases: a linear phase before gross slipping with a relatively high stiffness followed by a non-linear phase with gradually increasing stiffness (i.e. hardening). However, the analytical solution is capable of capturing the whole response with a remarkable accuracy when compared to the finite element model of the system constructed for cross-validation. This analytical solution facilitates studying the effects of various parameters on the behaviour of the system, namely, the coefficient of friction, pre-strain and geometrical aspect ratio. These parameters can be arbitrarily set to achieve a desirable behaviour of the system. The proposed system is capable of undergoing large deformations with symmetrical and stable hysteretic behaviour. The effectiveness of the proposed device in reducing the seismic responses of a building frame is examined using a simplified numerical model.